Thank you for the opportunity to help you with your question!
(2x^3y^(3/2))^(-2) / (x^(-1/2)y²)^(-2) = 2^(-2)x^(-6)y^(-3) / xy^-4 because (2x^3)^-2=2^(-2)x^(3*(-2))= =(1/4)x^(-6)
so : 2^(-2)x^(-6)y^(-3) / x^(1/2)y^4 = (1/(4x^6y^3)) / (x/y^4) = y^4 / 4x^7y^3 = y/4x^7
(2x^3y^(3/2))^(-2) / (x^(-1/2)y²)^(-2) = y/4x^7
if you don't understand something just ask
Each time you have any other homework just invite me i will give you the best answer ok
Can you do the top question as well number 4.
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?